Community Engagement and Human-Centered Design: Lessons From HEARS in Inclusive Recruitment of Older Adults. (17th December 2021) - Nieman, Carrie; Han, Hae-Ra; Marrone, Nicole; Suen, Jonathan; Szanton, Sarah; Trumbo, Jami; Lin, Frank
Abstract: Within hearing care, significant disparities persist despite the highly prevalent nature of age-related hearing loss and relatively few trials include representation of racial/ethnic minorities. HEARS is an affordable, accessible hearing care intervention delivered by older adult peer mentors. The HEARS randomized controlled trial (NCT03442296) is a community-engaged RCT with an embedded human-centered design practitioner. Recruitment efforts occurred over 18 months in partnership with 13 affordable housing and social centers. The cohort (n=151) includes 43% (n=65) who self-identify as African American and 63.6% (n=96) with <25, 000 annual household income. The cohort represents the largest to-date of African American and low-income older adults with hearing loss. Recruitment efforts entailed 470.5 staff hours and 4, 917.26 in supplies, equating to 1.4 hours and 14.13 per 1 individual screened and 3.1 hours and 32.56 for 1 participant randomized. Community-engaged research, partnered with human-centered design, may offer critical approaches to increasing representation within behavioral intervention trials.